Badāyiʿ-i mulaḥ : Nawhā-yi namakīn - al-Khwārazmī, Qāsim b. al-Ḥusayn (Miras Maktoob, ISBN: 9789004365452., 2019)
In the history of Arabic literature, the term adab ('custom', 'norm of conduct') applies typically to works providing a particular kind of moral and intellectual education. Aimed at a specific urban class whose values they reflected, these works offered a useful stock of relevant quotations to be used in social discourse. Among the adab works, the poetic anthology was extremely popular. These anthologies could take on different forms, depending on whether they were organised around a set of themes, a collection of motifs, a series of comparisons, a selection of geographical places, and so on. The poetic anthology published in the present volume was written in Khwārazm in 595/1199. As the title ' Marvels of Witticism ' suggests, its author, the linguist Qāsim b. al-Ḥusayn al-Khwārazmī (d. 617/1220), wanted to highlight the beauty of the repartee in different thematic contexts. The Persian translation accompanying the text was probably made by someone other than al-Khwārazmī himself.